Analysis of Academic Service Satisfaction Levels From the Perspective FTIK UNPRI Students Use the Method Importance Performance Analysis(IPA) - Angga Snidres Girsang; Elida Mardiana Manik; Egi Suranta Bangun; Saut Parsaoran Tamba (Sean Institute, 2022)
In the field of education, the level of comfort is an important service in activities. Especially students who are studying, lectures will be very enjoyable if the services provided are in line with expectations. In the academic section of the Prima Indonesia University campus, there are still many things that are beyond expectations. Especially in the academic service section, the level of student satisfaction has not been taken into account. Because there are still many students who do not feel that they have good facilities. So this study will test the academic services of the Prima Indonesia University campus. Student realities and expectations can be collected with questionnaire data. Students who are respondents will provide results in the form of a dataset that will be processed using the SPSS version 23 data processing application. The results of data testing will be carried out in the Importance Performance Analysis (IPA) method to get better and detailed results. The use of the IPA method will produce a catesian diagram as a result of the test. So that the results of the dataset are obtained to be used as conclusions in this study. From the results of the average level of conformity contained in the table for calculating the level of conformity. Got an average of 97%. Based on this, the level of service provided is close to the respondent's expectations. From the results of the average level of conformity contained in the table for calculating the level of conformity. Got an average of 97%. Based on this, the level of service provided is close to the respondent's expectations. From the results of the average level of conformity contained in the table for calculating the level of conformity. Got an average of 97%. Based on this, the level of service provided is close to the respondent's expectations.